Teachers’ professional identity: a multifactorial study in basic education institutions in metropolitan Lima - Herrera-Espinoza, Kelly; Gonzales-Saavedra, Fabianna; Pantigoso-Leython, Nathalí; Valverde-Alva, Weslyn; Colina-Ysea, Félix; Chavez-Ojeda, Mirelly; Diaz-Cornejo, Maria; Cruz-Gonzales, Richard; Varas-Rivera, Sindili; Terrones-Rodríguez, Elvis (Frontiers in Education, 2024)
Understanding teachers’ professional identity from a systemic viewpoint implies approaching the study from multifactorial elements. The research sought to determine the factors that explain teachers’ professional identity in public educational institutions in Metropolitan Lima, Peru, following a quantitative approach with a non-experimental, explanatory, and cross-sectional design. In this sense, the population was identified by teachers of the public educational institutions of Metropolitan Lima, and the sampling was convenient according to the accessibility of the researchers. The sample was defined as 510 teachers from 15 public educational institutions in Metropolitan Lima, 334 males and 176 females, aged between 23 and 64 years, from different working conditions, hired and appointed. The results show that the model composed of personal factors (gender, age, family burden, and civil status), labor factors (type of contract, length of service, type of educational institution, remuneration and training at the educational institution) and educational factors (level of studies, training center and number of preprofessional practice courses taken) explain the professional teaching identity as integrating elements that effectively contribute to the teaching practice. The influence of teacher training, the work center, and individual aspects on the teacher’s professional identity is corroborated.